Launched: Applications for CLIFF-GRADS Round 6 - Villarino, Ma. Eliza J. (2023)
The Climate, Food and Farming, Global Research Alliance Development Scholarships Programme, otherwise known as CLIFF-GRADS, is now open to receive applications for its sixth round of fellowships.